(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
The paper describes the findings of the implementation of Shift-Left Accessibility Engineering Framework (SLAEF) into an enterprise development setting. The results indicate that accessibility tests at the early stage assist the teams to identify more problems in the design phase and in the coding of the application, lower remediation time, and increase product quality. The framework also easily fits into the CI/CD pipelines with no deceleration in the delivery. Quantitative measures indicate that there are high improvements in the detection rates, reduced rework, faster fixes, and enhanced compliance to WCAG 2.2. The test of user experience establishes a reduced number of errors in navigation and satisfaction. The analysis demonstrates that the earlier the accessibility the higher the efficiency, stability and reliability in the long term